- 15 = 3X - 12
add 12 to each side
12 + - 15 = 3X - 12 + 12
- 3 = 3X
divide both sides integers by 3
- 3/3 = (3/3)X
- 1 = X
======check in original equation
- 15 = 3(- 1) - 12
- 15 = - 3 - 12
- 15 = - 15
=========checks
6x - 12 = 3x + 15 3x = 27 x = 9
15
15
3x - 12 = 10x - 15 - 6x -10 3x - 12 = 4x -25 3x + 13 = 4x 13 = 4x - 3x 13 = x None?
15
51.
x = 1
3x+12 = 18 3x = 18-12 3x = 6 x = 2
Well, if 3x equals 12, then x equals 4. And if y equals 3x, then y equals 3 times 4, which is 12. So, y equals 12. Math can be a piece of cake when you break it down like that!
If: 3x = 15 Then: x = 5
3x-4x=12 that means -x equals 12 so x equals -12
y = 15 (by transitivity)